Internationalization of Chinese SMEs: The role of networks and global value chains. Issue 2 (April 2020) - Su, Fang; Khan, Zaheer; Kyu Lew, Yong; Il Park, Byung; Shafi Choksy, Umair
This article examines the role of networks and global value chains (GVCs) and how they influence emerging economy small- and medium-sized enterprises' (EE-SMEs) internationalization. Drawing on the insights, experiences, and perspectives of entrepreneurs and senior managers of small- and medium-sized enterprises (SMEs) that have originated from China, the study adopts qualitative approach and examines nine firms' internationalization. We find that Chinese born-global manufacturing SMEs benefit from networks with quick insidership position into GVCs, but suffer from various obstacles that hinder their further development. The findings further indicate that network ties substantially facilitate EE-SMEs' internationalization, but also restrict their future global development, as their low position within the GVCs impedes further business development and capability building. The case firms' lower position within the GVCs weakens the networks' influence on their GVC upgrading. The research identifies key enablers of GVC engagement and obstacles of GVC upgrading of the case firms which play an important role in the EE-SMEs' internationalization. JEL CLASSIFICATION: M10; M16